PROPERTIES OF GUINEA PIG 7S ANTIBODIES : V. INHIBITION BY GUINEA PIGγ(1) ANTIBODIES OF PASSIVE IMMUNE LYSIS PROVOKED BYγ(2) ANTIBODIES - Kourilsky, F. M. (The Rockefeller University Press, 1963)
Passive immune lysis of antigen-coated erythrocytes provoked in vitro by guinea pig γ(2) antihapten antibodies in the presence of complement, is inhibited by guinea pig γ(1) antibodies directed against the same specificity. This inhibition of the lytic effect of complement-fixing γ(2) antibodies is presumably due to the competition for antigen by non-lytic γ(1) antibodies.